Hubungan Pemenuhan Kebutuhan Spiritual dengan Tingkat Depresi pada Lansia Penderita Diabetes Melitus - Aura Nhaha Putri Yasa, Putu Nanda; Mertha, I Made; Surasta, I Wayan; Wedri, Ni Made; Sukawana, I Wayan; Gede Ngurah, IGK (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2023)
The aging of an elderly will cause various problems in terms of psychology, physical, social and spiritual. Mental disorders such as depression become one of the problems that occur in elderly with diabetes mellitus due to living conditions that are not as expected. Spirituality can be used as a source of coping when experiencing sadness, loneliness or loss. The purpose of this study is to find out The Relationship Fulfillment of Spiritual Needs with Depression Levels in the Elderly with Diabetes Mellitus at Working Area Puskesmas I Denpasar Selatan in Year 2023. This research uses a quantitative research design with a non- experimental research design with a cross sectional approach. Sample of 76 respondents wereobtained by purposive sampling approach. This research instrument uses DSES (Daily Spiritual Exercise Scale) and GDS (Geriatric Depression Scale). Data analysis using Spearman's Rho Test with the level pa = 0.05 and showed the result of p = 0,000 and the correlation coefficient r = 0,729 which means that there is a strong relationship (0,51 0,75) between the two variables. Results of the study, so it can be concluded that there is a relationship between fulfillment of spiritual needs with depression levels in the elderly with diabetes mellitus at Working Area Puskesmas 1 Denpasar Selatan in 2023. It is recommended that health and family services fulfill the spiritual needs of the elderly through religious activities, love from the family to reduce depression in the elderly.